Bile acid signaling in skeletal muscle homeostasis: from molecular mechanisms to clinical applications - Jia, Feng; Liu, Xiangliang; Liu, Yahui (Frontiers in Endocrinology, 2025)
The intricate relationship between bile acid metabolism and skeletal muscle function has emerged as a crucial area of research in metabolic health. This review synthesizes current evidence highlighting the fundamental role of bile acids as key signaling molecules in muscle homeostasis and their therapeutic potential in muscle-related disorders. Recent advances in molecular biology and metabolomics have revealed that bile acids, beyond their classical role in lipid absorption, function as essential regulators of muscle mass and function through multiple signaling pathways, particularly via the nuclear receptor FXR and membrane receptor TGR5. Clinical studies have demonstrated significant associations between altered bile acid profiles and muscle wasting conditions, while experimental evidence has elucidated the underlying mechanisms linking bile acid signaling to muscle protein synthesis, energy metabolism, and regeneration capacity. We critically examine the emerging therapeutic strategies targeting bile acid pathways, including receptor-specific agonists, microbiome modulators, and personalized interventions based on individual bile acid profiles. Additionally, we discuss novel diagnostic approaches utilizing bile acid-based biomarkers and their potential in early detection and monitoring of muscle disorders. This review also addresses current challenges in standardization and clinical translation while highlighting promising future directions in this rapidly evolving field. Understanding the bile acid-muscle axis may provide new opportunities for developing targeted therapies for age-related muscle loss and metabolic diseases.